2000
DOI: 10.1088/0957-0233/11/7/306
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced fluorescence measurements in lean direct-injection spray flames: technique development and application

Abstract: The combustion diagnostics community has recently begun to focus its efforts toward practical combustion devices. One impetus behind this effort is the need to develop aeropropulsion gas turbine combustors with ultra-low NOx emissions. For the past several years, the Flame Diagnostics Laboratory at Purdue University has been advancing optically non-intrusive techniques to measure concentrations of nitric oxide [NO] in lean direct-injection (LDI) spray flames. LDI flames offer the possibility of reducing NOx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This technique has been successfully used in many studies of mixing process (Cooper and Laurendeau 2000;Gordon et al 2004;Liu et al 2008;Liu et al 2009;Luo et al 2006;Luo et al 2007;Nere et al 2003;Pan and Meng 2001;Thurber and Hanson 2001).…”
Section: Plif Techniquementioning
confidence: 99%
“…This technique has been successfully used in many studies of mixing process (Cooper and Laurendeau 2000;Gordon et al 2004;Liu et al 2008;Liu et al 2009;Luo et al 2006;Luo et al 2007;Nere et al 2003;Pan and Meng 2001;Thurber and Hanson 2001).…”
Section: Plif Techniquementioning
confidence: 99%
“…60 Narrowband monochromator detection ͑Ͻ5-nm bandpass͒ was used in most of the research for effective interference suppression; however, significant interference was observed with broadband imaging detection in the 4-bar spray flame. 55,61 In previous research, we investigated different transitions within the A-X͑0, 0͒ band in detail in premixed flat CH 4 -air flames up to 60 bar and discussed their applicability for high-pressure combustion situations. 4 It was shown that the transition originally proposed by DiRosa et al 24 is clearly superior to other approaches in terms of both signal strength and suppression of O 2 LIF interference.…”
Section: A-x͑0 0͒ Excitationmentioning
confidence: 99%
“…The sensitivity, therefore, is limited. Alternatively, other spectroscopy techniques based on the detection of absorption induced phenomena of light can be used such as pressure changes in photoacoustic spectroscopy [6], laser-induced fluorescence (LIF) [7,8], or ions in resonant enhanced multiphoton ionization (REMPI) [9]. But they are hard to calibrate.…”
Section: Introductionmentioning
confidence: 99%